Does food insecurity contribute towards depression? a cross-sectional study among the urban elderly in Malaysia - Mesbah, Siti Farhana; Sulaiman, Norhasmah; Mohd Shariff, Zalilah; Ibrahim, Zuriati (MDPI, 2020)
With the aging of the population worldwide, there is an increasing concern for the mental health status as well as physical health. Depression is a common mental health problem among the elderly populations. Since the elderly are susceptible to food insecurity, this cross-sectional study is aimed to determine an association between food insecurity and depression among elderly people. A total of 220 elderly people- aged 60 years and above, residing in the Petaling district of Selangor, were included in this study. Face-to-face interviews were conducted to obtain the pertinent information on demographic background, food security status (six items USDA FSSM), functional status (IADL, EMS), psychosocial status (LSNS-6), and depression status (GDS-15). Binary logistic regression was used to assess the factors that were associated with depression. The median age of the elderly sample was 65.5 years. The prevalence of depression and food insecurity that was recorded were 13.2% and 19.5%, respectively. Social isolation (AOR = 5.882, 95% CI: 2.221, 15.576), food insecurity (AOR = 3.539, 95% CI: 1.350, 9.279), and unsafe mobility (AOR= 3.729, 95% CI: 1.302, 10.683) increased the odds of depression. In conclusion, social isolation, food insecurity, and unsafe mobility are factors associated with depression among the elderly people. Plans such as health interventions as well as grocery and financial aid among the qualifying elderly are suggested to improve this depression and food insecurity.